COVID-19 vaccine confidence project for perinatal women (CCPP)—Development of a stepped-care model to address COVID-19 vaccine hesitancy in low and middle-income countries - Ransing, Ramdas; Raghuveer, Pracheth; Mhamunkar, Aman; Kukreti, Prerna; Puri, Manju; Patil, Suvarna; Pavithra, Hegde; Padma, Kumari; Kumar, Praveen; Ananthathirtha, Kavya; Goel, Manish Kumar; Deshpande, Smita N. (Frontiers in Public Health, 2023)
Background COVID-19 vaccine hesitancy (CVH) is common among perinatal women in low and middle-income countries (LMICs), but it is often unaddressed. This could be due to a lack of feasible, scalable, and acceptable interventions and models for CVH in LMICs. Our study aimed to develop a CVH intervention model that can be implemented in LMICs using existing human healthcare resources. Methods A literature review was conducted on aspects of vaccine hesitancy, pre-existing interventions, and models for addressing vaccine hesitancy (COVID-19 and non-COVID-19). The lead authors (RR and PKuk) formed a team consisting of vaccinators, experts, and stakeholders. Members shared their perspectives and proposals for various models and interventions that could be implemented in LMICs. A CVH intervention model was developed using a logic model, a WHO implementation toolkit, experts' feedback, and consensus. Results A consensus was reached to develop a COVID-19 Vaccine Confidence Project for Perinatal Women (CCPP), which is a primary health care worker (HCWs)-based stepped-care model. The CCPP model includes HCW training, integration into ongoing COVID-19 vaccination programs, CVH screening, CVH intervention, and referral services suitable for implementation in LMICs. Conclusion The CCPP project/model provides a practical approach that can help in the early detection and management of CVH. The model can be tailored to different healthcare settings to improve COVID-19 vaccine uptake among perinatal women in LMICs.